Do the functional properties of HCN1 mutants correlate with the clinical features in epileptic patients?. (November 2021) - Porro, Alessandro; Abbandonato, Gerardo; Veronesi, Valentina; Russo, Alberto; Binda, Anna; Antolini, Laura; Granata, Tiziana; Castellotti, Barbara; Marini, Carla; Moroni, Anna; DiFrancesco, Jacopo C.; Rivolta, Ilaria
Abstract: The altered function of the Hyperpolarization-activated Cyclic-Nucleotide-gated (HCN) ion channels plays an important role in the pathogenesis of epilepsy in humans. In particular, HCN1 missense mutations have been recently identified in patients with different epileptic phenotypes, varying from mild to severe. Their electrophysiological characterization shows that mutated channels can act both with loss-of-function and gain-of-function mechanisms of action, without an evident correlation with the phenotype. In search for a correlation between clinical features and biophysical properties of the mutations, in this work we considered sixteen HCN1 mutations, found in eighteen Early Infantile Epileptic Encephalopathy (EIEE) patients. Statistical analysis did not establish any significant correlation between the clinical parameters and the current properties of the mutant channels. The lack of significance of our results could depend on the small number of mutations analyzed, epilepsy-associated with certainty. With the progressive increase of Next Generation Sequencing in patients with early-onset epilepsy, it is expected that the number of patients with HCN1 mutations will grow steadily. Functional characterization of epilepsy-associated HCN1 mutations remains a fundamental tool for a better understanding of the pathogenetic mechanisms leading to the disease in humans.